The level of awareness by professionals of management practise in conservation project / Nor Islahiah Hashim - Hashim, Nor Islahiah (2007)
Malaysia is one of the most beautiful countries in this world. The beautiful environment with multicultural heritage is the attractions. Historical buildings have significant cultural value and should be considered as precious structural monuments. Building conservation has long been a concern although its popular application is relatively recent in origin. Being custody of future generation, the obligation has to be fulfilled.